The Practitioner and School Age Child Problems - Teicher, Joseph D. (1969)
The extraordinary plasticity of the growing child offers the general practitioner an unusual opportunity to intervene either in a preventative or therapeutic manner. Such intervention, properly the task of any informed physician dealing with families, can alter unhealthy growth to healthier development. The whole child is just as important as his medical illnesses; the whole family usually needs help when there is an emotional disturbance in any child. Common problems that lend themselves readily to physician intervention are behavior disorders accompanying a neurological deficit, conduct disorders, enuresis and school phobias. Knowing how to elicit information, to evaluate clinical data and to utilize the findings of a skilled psychologist, and when to refer to a psychiatrist, plus a thorough knowledge of community resources are part and parcel of a physician's equipment for dealing with children and families.